Strategi Pemasaran Usaha Jasa Konstruksi dalam Menghadapi Kondisi Turunnya Pasar Konstruksi Swasta (Studi Kasus Pt. Xx-Divisi Gedung) - Deddy Arief Himawan; Nurul Yaqin; Hadiah Fitriyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The presence of the Covid-19 pandemic has brought changes to the world with various challenges that were never imagined before. Efforts to prevent the spread of the Covid-19 virus have hampered economic activity, including the construction sector, which makes a major contribution to the economy. This study aims to analyze the marketing strategy in dealing with the declining condition of the private construction market so that it can determine the construction market segmentation during the Covid-19 pandemic, to find out the marketing strategy in 2021 refers to the marketing realization in 2020, the condition is that the private sector marketing in 2020 is very little and Many private sector projects obtained in 2020 are of low quality. For this purpose, a large amount of data was collected through literature study, descriptive qualitative and focus group discussions. Here, we present primary data taken from the marketing data of PT. XX – Building Division in 2020, while secondary data comes from books, journals or other literary sources. From primary data, the results show that the construction market in 2020 experienced a decline, especially in the private sector. For that, in 2021 PT. XX – The Building Division carries out a marketing strategy, namely in the government sector including BUMN, because many private sector construction works are delayed or neglected. In addition, the marketing strategy carried out by PT. XX – Building Division is to focus on local government owners who have potential so that it is hoped that marketing targets can be achieved according to the company's prognosis.